PENGUKURAN KINERJA SUMBER DAYA MANUSIA MENGGUNAKAN METODE HUMAN RESOURCE SCORECARD - Aulia Karlina; Didi Samanhudi (Universitas Ahmad Dahlan, 2023)
In recent research, employee performance evaluations have not been carried out comprehensively. However, problems related to employee performance are the increasing number of complaints and the achievement of project targets on time. This study aims to determine the level of employee performance and provide suggestions for improving key performance indicator (KPI) below the target. The sampling method is non-probability sampling with purposive sampling. The method used is the Human Resource Scorecard (HRS) supported by the Analytical Hierarchy Process (AHP) and Traffic Light System (TLS). The results showed that the performance measurement score of PT. Modern Pulsa Investama in 2021 is 2,23 (less) with a TLS of 2,90; in 2022, it is 2,99 (medium), with a TLS of 5,86, indicating satisfactory performance. Based on 15 KPIs in 2021, 4 were obtained in the green group, 5 in the yellow group, and 6 in the red group. Of the 15 KPIs in 2022, 6 were obtained in the green group, 6 in the yellow group, and 3 in the red group. KPIs that go on a yellow to red scale are the focus of improvement. PT. Modern Pulsa Investama is a company that develops bill payment applications and online product purchases.